2014
DOI: 10.2478/s11686-014-0264-9
|View full text |Cite
|
Sign up to set email alerts
|

Seven new species of helminths for reptiles from Armenia

Abstract: Helminthic infections of reptiles habiting in the territory of Armenia are examined. Seven species of helminths new for reptiles from Armenia are registered: Parapharyngodon skrjabini, Oswaldocruzia goezei, Neoxysomatium sp., Telorchis assula, Nematotaenia tarentolae, Mesocestoides lineatus and Spirometra erinacei europea. Descriptions and pictures of them are given.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Other reported reptilian hosts : The genus Mesocestoides is cosmopolitian and tetrathyridia can be found in all classes of vertebrates. We have listed known accidental or paratenic hosts reported from the Palearctic biogeographic region: Slow worm, Anguis fragilis (Lewin, 1990); Mongolian racerunner, Eremias argus (Dugarov et al, 2018); Sand lizard, Lacerta agilis (Nelli et al, 2014; Lewin, 1992a; Sharpilo et al, 2001); Redbelly rock agama, Paralaudakia erythrogaster (reported as Agama erythrogaster , Radchenko, 1973); Eastern giant emerald lizard, Lacerta media (Nelli et al, 2014); Iberian emerald lizard, Lacerta schreiberi (Roca & Ferragut, 1989); Lacerta viridis (Biserkov & Kostadinova, 1998); Snake-eyed lizard, Ophisops elegans (Nelli et al, 2014); Secret toadhead agama, Phrynocephalus mystaceus (Ikromov & Cho, 2004); Bocage’s wall lizard, Podarcis bocagei (Roca et al, 1989); Iberian wall lizard, Podarcis hispanica (Roca et al, 1989); Common wall lizard, Podarcis muralis (Kirin, 2002a); Ibiza wall lizard, Podarcis pityusensis (Roca & Hornero, 1991; Roca & Hornero, 1994); Spanish psammodromus, Psammodromus hispanicus (Roca et al, 1986a; Roca & Lluch, 1988); Tenerife wall gecko, Tarentola delalandii (Roca et al, 1987); Smooth snake, Coronella austriaca (Biserkov, 1996); Western whip snake, Hierophis viridiflvus (Santoro et al, 2013); Aesculapean snake, Zamenis longissimus , (reported as Elaphe longissima , Biserkov, 1996); Halys pit viper, Gloydius halys (reported as Ancystrodon halys , Bogdanov et al, 1969); European grass snake, Natrix natrix (Lewin, 1992b); nose-horned viper, Vipera ammodytes (Biserkov, 1995).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other reported reptilian hosts : The genus Mesocestoides is cosmopolitian and tetrathyridia can be found in all classes of vertebrates. We have listed known accidental or paratenic hosts reported from the Palearctic biogeographic region: Slow worm, Anguis fragilis (Lewin, 1990); Mongolian racerunner, Eremias argus (Dugarov et al, 2018); Sand lizard, Lacerta agilis (Nelli et al, 2014; Lewin, 1992a; Sharpilo et al, 2001); Redbelly rock agama, Paralaudakia erythrogaster (reported as Agama erythrogaster , Radchenko, 1973); Eastern giant emerald lizard, Lacerta media (Nelli et al, 2014); Iberian emerald lizard, Lacerta schreiberi (Roca & Ferragut, 1989); Lacerta viridis (Biserkov & Kostadinova, 1998); Snake-eyed lizard, Ophisops elegans (Nelli et al, 2014); Secret toadhead agama, Phrynocephalus mystaceus (Ikromov & Cho, 2004); Bocage’s wall lizard, Podarcis bocagei (Roca et al, 1989); Iberian wall lizard, Podarcis hispanica (Roca et al, 1989); Common wall lizard, Podarcis muralis (Kirin, 2002a); Ibiza wall lizard, Podarcis pityusensis (Roca & Hornero, 1991; Roca & Hornero, 1994); Spanish psammodromus, Psammodromus hispanicus (Roca et al, 1986a; Roca & Lluch, 1988); Tenerife wall gecko, Tarentola delalandii (Roca et al, 1987); Smooth snake, Coronella austriaca (Biserkov, 1996); Western whip snake, Hierophis viridiflvus (Santoro et al, 2013); Aesculapean snake, Zamenis longissimus , (reported as Elaphe longissima , Biserkov, 1996); Halys pit viper, Gloydius halys (reported as Ancystrodon halys , Bogdanov et al, 1969); European grass snake, Natrix natrix (Lewin, 1992b); nose-horned viper, Vipera ammodytes (Biserkov, 1995).…”
Section: Resultsmentioning
confidence: 99%
“…In two reports related to Ophisops elegans , Goldberg and Bursey (2010) examined Iranian species and came across Oochoristica tuberculata and Nelli et al (2014) encountered Mesocestoides lineatus in Armenian species. Nothing has been published on helminths of P. muralis, P. siculus and O. elegans from Bursa province, North-western Turkey.…”
Section: Introductionmentioning
confidence: 99%
“…in reptiles in Europe, and the first infected reptiles in Poland. In Asia, where this tapeworm occurs frequently, many species of snakes act as second intermediate hosts (Wang et al 2011(Wang et al , 2014Nelli et al 2014). Reptiles infected with spargana were also recorded in South America (Oda et al 2016), Australia (Zhu et al 2002), and Africa (Pantchev and Tappe 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Intermediate hosts for Spirometra sp., such as amphibians and reptiles, are already considered important vectors for parasite transmission in Asia (Wang et al 2011(Wang et al , 2014Nelli et al 2014;Hong et al 2016). In Europe, the only three cases of infected reptiles, in a common European viper (Vipera berus) and a grass snake (Natrix natrix), have been recorded in Italy, Germany, and Belarus (Joyeux and Baer 1927;Odening et al 1980;Shimalov et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported for Iraq as Camallanus microcephalum from the Caspian turtle by [38] widely geographical distributed in the north of Iraq but with relatively low prevalence. This nematode was frequently recorded in various freshwater turtle species, in Emys blandingii [39]; Chrysemys picta, Chelydra serpentina, Clemmys insculpta and Emys blandingii [40] ; Emys orbicularis [41]; Chrysemys picta [42] ; Mauremys leprosa [43] ; Trachemys scriptaelegans [37] ; Trachemys scripta and Pseudemys concinna [27] and Mauremys caspica [28] . The mean intensity of this parasite in the present study is 4.3 (Tab.…”
Section: Malementioning
confidence: 99%